Pulse oxygen saturation in healthy newborns at term in Cusco, Peru - Hurtado A. (2006)
This study was supported by a grant from theConsejo Nacional de Ciencia, Tecnología e Innova-ción Tecnológica (CONCYTEC), Lima, Peru.